Adsorption and enrichment of simulated 137Cs in geopolymer foams. Issue 4 (August 2021) - Xiang, Yi; Hou, Li; Liu, Jiamin; Li, Jun; Lu, Zhongyuan; Niu, Yunhui
Abstract: Separation and removal of 137 Cs with long decay period and high decay heat will be beneficial to the subsequent treatment and disposal of radioactive wastes. In this study, geopolymer foams (GFs) with proper mechanical performance and density of 300–600 kg/m 3 have been prepared through prefabricated foam method, which were proposed to be used as the adsorbent monoliths for 137 Cs based on its zeolite-like and hierarchical micro- and meso- pore structures. The prepared bulk GF exhibited remarkable adsorption capacity (192.14 mg/g) and desorption efficiency (64.92%) for simulated 137 Cs in aqueous solution. Furthermore, the adsorption process followed Pseudo-second-order kinetic and Langmuir isotherm models, which was also spontaneous, endothermic, and entropy increased. Finally, the adsorption and enrichment mechanism of simulated 137 Cs in GFs was thus proposed. Graphical Abstract: The figure shows the mechanism of Cs + adsorption by GF. The Cs + adsorption process is dominated by chemical adsorption includes ion-exchange and cation compensation mechanism. And also, physical adsorption exists as electrostatic attraction and hydrogen bonds interaction. ga1 Highlights: Hierarchical pore structure of GFs was formed during consolidation of GFs. High adsorption capacity (192.14 mg/g) of Cs + was achieved by bulk-type GFs. GF is potential to be directly used as a self-supporting adsorbent or filter for removing 137 Cs.